ANALISIS KESESUAIAN BUKU SISWA KELAS IV BERBASIS KURIKULUM 2013 TEMA “PAHLAWANKU” SUBTEMA “PERJUANGAN PARA PAHLAWAN” - Indriasari, Bernadine Ajeng (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2018)
ABSTRACTThe purpose of this research is to know stundent book of four grade student based on Curricullum 2013 on theme “Pahlawanku” on subtheme “Perjuangan Para Pahlawan” on fisrt learning activities with kompetensi dasar, purpose, indicator, learning activity, materials, tool and learning resources. Research method is descriptive method by analyze document is student book of four grade student based on Curricullum 2013 ontheme “Pahlawanku” and teacher book of four grade student based on Curricullum 2013. The analize revolves on the rule of Menteri Pendidikan dan Kebudayaan Nasional, an article discussing about the implementation of Curricullum 2013 and article from Badan Nasional Standar Pendidikan (BSNP) website. The result of this research are found that some kompetensi dasar less related. Indicator is too narrow. Purpose of learning is not according with the indicators. Less meaningfull learning activities. The material is too shallow. Also there is no tools and learning media are suggested to support learning activities. As the conclusions, student bood of four grade student theme “Pahlawanku” needs much improved with the discrepancies in first learning activities on subtheme “Perjuangan Para Pahlawan”.Keywords: Analyze, Student book, Curricullum 2013